Growth determinants of start-ups in Eastern Germany: a comparison between innovative and non-innovative firms - Matthias Almus; Eric A. Nerlinger; Fabian Steil (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
This empirical analysis deals with the determinants of growth and the explanation of variations in the growth between innovative and non-innovative start-ups. Based on theoretical models explaining the growth of firms, hypotheses on potential determinants are formulated. The regression results indicate strong correlations between the growth rate on the one side and firmspecific, founder-specific as well as external factors on the other side. These factors influence the growth rates of innovative and non-innovative young firms in different ways. It becomes obvious that large and mature firms have smaller growth rates than small and young innovative as well as non-innovative firms. Moreover, other firm-specific characteristics like legal form and formal links to other firms from Western industrialised countries have an impact on the development of start-ups. With respect to founder-specific characteristics, positive effects can be derived from the human capital of the founder(s). This holds especially for technological disciplines whereas business knowledge plays a minor role. In addition to firm and founder characteristics, locationspecific factors controlling for agglomeration effects and the industry structure in the Eastern German counties have an impact on growth. Comparing annual growth rates of start-ups, innovative start-ups grow on average faster than non-innovative start-ups.
Keywords: J23; D92; L11; 330; New Technology-based Firms; Employment Growth; Determinants of Growth; Unternehmensgründung; Verarbeitendes Gewerbe; Unternehmensentwicklung; Beschäftigungseffekt; Innovation; Schätzung; Neue Bundesländer